MENYEDIAKAN INFORMASI PRAKIRAAN LOKASI POTENSI DAN PENANGKAPAN IKAN SELAMA MUSIM BARAT DI PERAIRAN TELUK CENDERAWASIH - Alianto (Yayasan Nusantara Hasana Berdikari, 2023)
This community service aims to provide information on potential location forecasts and fishing for fishing industries and fishermen operating in the waters of Cenderawasih Bay. Information on the location forecast of fish and fishing potential is obtained secondarily. During the western season, 37 potential fish locations were obtained and 9 fishing locations.. There were 17 potential fish locations in January and 4 fishing locations. The potential location of fish in February was 9 locations and fishing was 1 location. The potential locations of fish in March were 11 locations and fishing locations were 4 locations. The location of fish potential in the waters of Nabire Regency, Waropen, Memberamo Raya, Yapen Islands, Wondama Bay, between Yapen Islands and Wondama Bay, between Biak Numfor and Yapen Islands, between Yapen Islands and Memberamo Raya, between Biak Numfor and Memberamo Raya successively as many as 10 locations, 6 locations, 6 locations, 2 locations, 4 locations, 3 locations, 2 locations, 1 location, 1 location. Fishing locations in the waters of Nabire Regency, Waropen, Wondama Bay, between Yapen Islands and Wondama Bay, between Yapen Islands and Memberamo Raya are successively 3 locations, 1 location, 1 location, 1 location, 3 locations.